Optimization design parameter of dual mass flywheel coupled with a non-linear elastic path - Karakuş, Gökay (Graduate School, 2023)
Today, expectations from automotive industry are high in the fields of performance, comfort, economy and environmental protection. That is why, the automotive industry must have a knowledge, experience, development processes, and strong research. Hence, the design of the components that transmit power from the internal combustion engine to the wheels via axes in a vehicle are crucial research topics. The flywheel, which is the primary element in power transmission system, works in engine in order to reduce the speed fluctuations on the crankshaft. Along with the studies in the field of flywheel development, dual-mass flywheels have been started to be used as an alternative to the single-mass flywheel. Briefly, the dual mass flywheel can be defined as the combination of two single mass flywheels. The spring damper system is combined with these two single mass flywheels. The dual-mass flywheel, which is used in diesel engines, is thought to have favorable effects on the dynamics of the power transmission system compared to the single-mass flywheel. In 1985, the first dual mass flywheel (DMF) was manufactured in automotive sector. In begin, dampers in flywheel were not lubricated and the springs are stand away from outside and created some wear problems. In 1987, DMF is lubricated with grease oil for the first time. Service life problem was no longer an issue thanks to grease oil application. Around 1989, arc spring damper was innovation for the DMF, and it had pretty much solved all resonance problems. Alson manufacturing costs were continually reduced. The primary mass of flywheel was made by casting or forged steel at first production batches. Over time, the primary mass was formed from sheet metal parts by metal-forming specialists. In 1995, folded masses were developed from sheet metal in order to increase inertia moment of primary mass of flywheel. This development led to the widespread use of the DMF. However, there is some disadvantages such as cost, the achievable improvements are seen clearly, therefore, DMF are used widespread in vehicles. There are some advantages of dual mass flywheel such as isolation from torsional vibration, relief of transmission and crankshaft. Within the scope of this study, firstly, give information about flywheel, parts of dual mass flywheel and its advantages. Then, while engine is running, the working principles of dual mass flywheel is mentioned. Also, the single mass flywheel and dual mass flywheel are compared and it has been observed that the resonance regions are reduced below the engine idle speed with the use of dual-mass flywheel. After all crucial information was explained, mathematical model of DMF is built. The model was solved in Matlab for all optimization. Sensitivity analysis was done in order to determine the parameter effects on system. The design parameters were determined as stiffness ratio, damping ratio and inertia ratio. Also, the system was running on non-linear cubic path, that is why, non-linear stiffness ratio is also important parameter to examine system correctly. The primary body represent not only primary flywheel itself but also engine side dynamic properties.
Lineer olmayan elastik yol ile çalışan çift kütleli volan tasarım parametreleri optimizasyonu
Thesis (M.Sc.) -- İstanbul Technical University, Graduate School, 2023
Keywords: Dual Mass Flywheel; torsional vibrations; time domain